Enhancing Corporate Governance: Female Board Influence on Non-Financial Reporting Effectiveness in Managing Agency Costs - Nicken Destriana; Shalma Atika Putri (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study examines how non-financial disclosures influence agency costs in Indonesian manufacturing companies, emphasizing the moderating effect of female board members. It offers a new perspective on corporate governance by exploring the female board's role in this relationship.Methodology: Using secondary data from 32 manufacturing companies listed on the Indonesia Stock Exchange from 2021-2023, the research employs multiple linear regression and purposive sampling. Agency costs are proxied by two expense ratios and an asset utilization ratio.Findings: Non-financial disclosures significantly impact agency costs. Female board representation strengthens this relationship for expense ratio measures, suggesting enhanced transparency and reduced agency costs. However, this moderating effect is not significant when agency costs are measured by the asset utilization ratio, implying female board members are more effective in moderating operational agency costs than investment-related ones.Conclusion: This research uniquely shows how gender dynamics on boards affect non-financial disclosure's effectiveness in mitigating agency costs within a male-dominated manufacturing sector. It offers valuable insights for corporate governance and investment practices.